EPROPOSAL FOR AN EVENT RECONSTRUCTION ALGORITHM TO STUDY THE EVOLUTION OF CANCEROUS CELLS - Calderón Ch, J. Alan (2022)
In this work, a general algorithm is proposed to design the reconstruction of chemical/physical/biological process events as one of the most complicated today: the evolution of cancer cells. Studying the evolution of the boundary curves it is possible to make a three-dimensional (3D) integration, in addition the 3D figure obtained can be explained through a mathematical model to estimate its geometric evolution after physical/chemical reactions. In this work, there are analyzed images of each stage of the process based on the evolution of cancer cells. Each image was processed in order to obtain a mathematical equation as a reference to understand the geometry of the 3D structure based on its 2D image for each stage. On the other side, with this information and the processing of each stage image, a mathematical equation was achieved to describe the geometry of the structure between stages by "Optimal Prediction Analysis" which is so important to gain understanding of the geometry of the structure with the internal process.